Subcutaneous splenosis - San Martín, Pablo D.; Sibona, Flavia C. (Revista Argentina de Cirugía, 2026)
Splenosis is the result of seeding and implantation of splenic tissue in any part of the body, usually as the consequence of accidental or iatrogenic splenic injury. The most common location is the peritoneal cavity, but it can also occur in other extraperitoneal sites such as the thorax or subcutaneous tissue. We present the case of a 63-year-old male patient with pain below the left scapula associated with a tumor that had grown progressively over time. The patient had a history of histiocytosis treated with chemotherapy, COVID-19 and a gunshot injury with the entry site in the left posterior axillary line. The magnetic resonance imaging detected lesions within the subcutaneous tissue among the fibers of the latissimus dorsi muscle. The lesion was surgically resected. The pathology examination reported subcutaneous splenosis, a rare condition. SARS-CoV-2 infection could produce systemic changes in the heterotopic splenic pulp and could be the reason for the late development of the disease.